Thesis and dissertation subject metadata in repositories: an exploratory study on vocabulary control - Lopes Fujita, Mariangela Spotti [UNESP]; Barros Ribas, Rosane Rodrigues de [UNESP]; Scarpino Rodrigues, Milena Maria [UNESP]; Dias Silveira, Telma Jaqueline [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The metadata of theses and dissertations are inserted in the repositories automatically or manually, in Dublin Core format, different from the one used by the libraries, generating duplicity of work. The objective is to compare the procedures of thematic treatment of theses and dissertations existing in the online catalogue and in the repository, through the analysis of subject metadata. An exploratory study was carried out with a case study on the use of vocabulary control in theses and dissertations metadata, with the institutional repository of sao Paulo State University and the Athena online catalog of the same institution. The exploratory study had two stages: documentary study of the historical trajectory of treatment of theses and dissertations at university and analysis of procedures of thematic treatment of theses and dissertations in databases, by authors and catalogers. The analysis of thematic treatment procedures employed observation of functioning and of routines and patterns, for evaluation of vocabulary control in the analysis of subject metadata. The results obtained revealed that the vocabulary control is not done in the search interfaces for information retrieval and neither in the alphabetical list of keywords, which means lack of guidance to authors, regarding the assignment of descriptors. The analyses showed two thematic treatments, which results in different subject representations, in natural language, in the repository, and in controlled language, in the catalogue. Two proposals were elaborated for the thematic treatment in subject metadata of theses and dissertations in repositories and library catalogues. It is concluded that the proposals may be assisted by the elaboration of an indexing policy of the repository that foresees the sharing of data resulting from self-archiving of theses and dissertations with the catalogue and that can accept the attribution of controlled vocabulary descriptors, besides the attribution of keywords.
Keywords: subject metadata; institutional repositories; dissertations; theses; indexing policy